Prevalence of myopia among school going children - Hittalamani, Suresh B.; Jivangi, Vivekanand S. (International Journal of Research in Medical Sciences, 2017)
Background: Poor vision in childhood affects performance in school or at work and has a negative influence on the future life of the child. Moreover planning of a youth’s career is very much dependent on the visual acuity, especially in jobs for navy, military, railways and aviation. This warrants early detection and treatment of refractive errors to prevent permanent disability.Hence present study was planned with the objective to determine, the prevalence of myopia among school children. Methods: An institution based cross sectional study was carried out among primary and high school children of 7 – 15 years of age. A total of 4429 children were studied over a period of one year. Visual acuity was performed among all children. Myopic children were referred for further evaluation and management. Data was entered in excel and analyzed using proportions and chi square test. Results: The prevalence of myopia was 6%. It was more among girls 155 (58.27%) than boys 111 (41.73%) were boys. 91.73% had bilateral myopia. Visual acuity improved in 95% of cases after correction. Myopia was more common among social class IV compared to social class VI. Conclusions: Early diagnosis and visual rehabilitation of myopic students can be achieved by periodic eye examination at regular intervals by school teachers and basic health workers and this can help in preventing the development of amblyopia thereby reducing the burden of morbidity due to myopia.